(untitled) (JURNAL ADMINISTRASI PUBLIK, 2016)
ABSTRACT :The role of the Regional Employment Board is not optimally manage personnel resources, it is necessary to improve the quality of personnel resources in improving the professional performance of the apparatus, especially for professional development related to management skills. The population in this study were all officers or employees in Sub Tobelo North Halmahera recorded the number of officers or employees who have as many as 25 civil servants. The research method that I use in this study is a quantitative research methods. The methods and approach used by the consideration that examined in this study is quite actual and factual and intends to examine the relationship or influence between the variables. The results of product moment correlation analysis and simple regression, can be tested the hypothesis that "Education and training influence on Organizational Performance Regional Employment Board of North Halmahera District", the 1% significance level, indicating that education and training are very influential on Organizational Performance, especially in the office of the Regional Employment Board Halmahera north, the magnitude of these effects can be observed from the analysis of determination, where the coefficient of determination obtained for 0.894 which may be interpreted that the magnitude of the influence of education and training to organizational performance 89.4%. These results indicate that the variation change of organizational performance by an average of 41.79, or 69.65% is determined by a variety 89.4%, while theï‚±of factors change Education and Training of remaining 10.6% influenced. data analysis showed that between education and training the performance of the organization has linkage relationships and influences that are contributive as well as the very real or significant. Keywords: education and training, organizational performance